2020
DOI: 10.3389/fmars.2019.00795
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perspectives on Opportunities and Challenges in Achieving Sustainable Growth of the Blue Economy in a Changing Climate

Abstract: Coastal marine environments provide livelihoods as billions of people around the world depend greatly on sustainability efforts in the Blue Economy. In this study, we investigated how stakeholders from important Blue Economy sectors along the German North Sea coast perceive the impacts of climate change on their daily work life and the growth of the Blue Economy. In a two-stage approach we first conducted two stakeholder workshops with representatives from the regional sea food sector, science, NGOs and local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
0
17
0
2
Order By: Relevance
“…Decisions could influence the sustainable growth of the BE in highly contested regions because both companies and political authorities are influenced by economic interests and by stakeholders that have power in decision-making. This could result in sustainable growth having a stronger influence than the effects of climate change, making it a more flexible and adaptable approach to policymaking that considers changing economic, social, and environmental realities [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decisions could influence the sustainable growth of the BE in highly contested regions because both companies and political authorities are influenced by economic interests and by stakeholders that have power in decision-making. This could result in sustainable growth having a stronger influence than the effects of climate change, making it a more flexible and adaptable approach to policymaking that considers changing economic, social, and environmental realities [56].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increase in human activity, in the form of new or intensified uses, such as the generation of renewable marine energy, exert greater influence and cause conflicts between BE sectors [56].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been found that the synergies, con icts between sectors, and political decisions could in uence the sustainable growth of the BE in highly contested regions such as the North Sea basin. This could result in sustainable growth having a stronger in uence than the effects of climate change, making it a more exible and adaptable approach to policymaking that considers changing economic, social, and environmental realities (Hoerterer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Linking BE with SDGs is challenging, and con ict areas exist primarily around divergent views on the legitimacy of different sectors as components of BE, particularly high carbon-intensive industries such as oil and gas and the emerging seabed mining industry . Furthermore, the increase in human activity, in the form of new or intensi ed uses, such as the generation of renewable marine energy, exert greater in uence and cause con icts between BE sectors (Hoerterer et al, 2020 Biotechnology presents excellent opportunities to produce natural products with possible applications in the food and pharmaceutical sectors (Rotter et al, 2020;Skrzeszewska & Beran, 2016). It is a recent and developing sector that is part of the bioeconomy, the latter developing and using renewable biological resources from the land and sea.…”
Section: Colgan 2013mentioning
confidence: 99%
“…Developing a sustainable Blue sea is the dream of every ocean economy but many questions regarding blue growth remains untargeted at the time of making policies as ocean economy is a combination of natural capital inputs (generated from sea) and human or manmade capital inputs so it is important that Governments of these nations must identify the economic worth of their oceans and design policies that connects all actors and ensure economic activities by identifying the loop holes and the entry points that will change the flow of inputs from marine eco-system to marine or blue economy (Patil, et al, 2018). Maintenance of sea environment is an important aspect of sustainable blue economy and its degradation will impact the entire humanity so, it is important to engage the stakeholders in achieving the environmental targets as their lives are largely depends on oceans so, policy making is not effective unless the three main components of blue economy are not synchronized and these components are Policy makers, economic stake holders and societal stakeholders because policy actions have quick visibility while the climate change is a social and economic reality which will impact slowly but dangerously so sustainability requires the participation of every component (Hoerterer, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%